An Analysis of How Language Forms Cross-Cultural Ties: Analisis tentang Bagaimana Bahasa Membentuk Ikatan Lintas Budaya - Dushatova Shohsanam Baxtiyor qizi; Yusupov Husanboy Faxriddin o’g’li (Academia Open, 2022)
This scientific article explores the significance of language in various cultures, emphasizing its diversity and linguistic aspects, as well as its profound impact on human comprehension of foreign cultures. Drawing on the leading theoretical perspectives of international scholars, our study aims to investigate the goals, methods, results, and implications of language's role in fostering cross-cultural understanding. Through meticulous analysis and synthesis of relevant literature, we elucidate the multifaceted nature of language's influence on cultural comprehension, highlighting the intricate interplay between language, culture, and identity. Our findings underscore the critical importance of linguistic diversity in appreciating and comprehending diverse cultures, paving the way for enhanced intercultural communication and fostering global harmony. Highlights: Language as a Key to Cultural Understanding: The article emphasizes the pivotal role of language in facilitating cross-cultural comprehension, serving as a gateway to unraveling the intricacies of diverse cultures and promoting intercultural dialogue. Linguistic Diversity and Cultural Identity: By exploring the linguistic aspects of different cultures, this research sheds light on how language shapes and reflects cultural identities, highlighting the significance of linguistic diversity in appreciating and preserving cultural heritage. Implications for Enhanced Intercultural Communication: The findings of this study carry significant implications for fostering effective intercultural communication, emphasizing the need for embracing linguistic diversity and promoting language education as a means to bridge cultural gaps and promote global harmony. Keywords: language diversity, cross-cultural understanding, linguistic aspects, cultural comprehension, intercultural communication